Quantifying economic risks to dairy farms from volcanic hazards in Taranaki, Aotearoa / New Zealand - McDonald NJ; Dowling L; Harvey EP; Weir AM; Bebbington MS; Bui N; Magill C; Craig HM; Mcdonald GW; Monge JJ; Cronin SJ; Wilson TM; et al. (Copernicus Publications on behalf of the European Geosciences Union, 2025)
The volcanic hazard and risk science for Taranaki Mounga (Taranaki volcano) in Aotearoa / New Zealand is in an advanced state, with robust probabilistic data and a series of direct impact scenarios modelled for the region. Here, we progress this work and demonstrate a method to provide risk information that is nuanced for factors such as location and economic sector and considers the dynamic nature of volcanism with hazards potentially repeated over time. Recognising the fundamental importance of the dairy sector to Taranaki region, this paper provides valuable insights into the potential impacts and risks to heterogeneous dairy cattle farms within the region from volcanic hazards. We provide volcanic impact and risk metrics in economic or monetary terms in order to improve its relevance to decision-makers while reducing the complexity of the impacts. To do this, we developed a dynamic, multi-event farm system model of response and recovery, which takes in hazard intensity metrics from a series of volcanic events and generates the resulting annualised revenues, expenditures, and recovery costs through time. The model is formulated in a generalised way such that it can be used for various other hazard types and agricultural land uses. In our application of the model, we create and apply a suite of 10 000 simulations that capture different iterations of possible future volcanic activity over a 50-year period. These include the generation of lahars following eruptions and associated failures for transport and water supply networks. Farms at five case study locations were modelled to capture the diversity in farm management and the spatial variation in hazard intensities and likelihoods across the region. We provide summaries of the distributions of economic impacts generated, both for individual events and for the 50-year volcanic future horizon. Drawing the information together, we also summarise the results for each case study farm in terms of the value at risk statistic. For the case study farms with negligible lahar risk, we find, with 90 % confidence, that volcanic losses over the next 50 years will not exceed around 10 % of property value. By comparison, for the farm with the most severe lahar and ashfall exposure, we find that, at the same level of confidence, losses extend to approximately half the property value. These results indicate that with access to sufficient risk information, we should anticipate volcanic risk as playing an important role in shaping the future dairy sector in Taranaki region. The modelling pipeline and assessment metrics demonstrated in this paper could be used to assess mitigation and adaptation strategies to reduce the risk from volcanic hazards and improve the resilience of farm businesses.